A case study of training and development program in the hotel industry of Malang - Khoirul Anam; Siti Asiyah; Pardiman - (Universitas Merdeka Malang, 2023)
Human resources are very important assets for a company in supporting the achievement of goals, so it is a must and necessity for organizations to improve the ability and competence of employees through training and development. Training and development programs aim to ensure that employees acquire the necessary knowledge, skills, competencies, and attitudes to carry out tasks and achieve organizational goals and objectives. This study aims to determine the training and development programs carried out by four-star hotels in the city of Malang. The research subject was a Human Resources Manager who had a training and development program in his organization with a total of 68 employees. The type of research used is a qualitative case study model with research data collection through observation, interviews, and documentation. Various training and development activities are very diverse, but excellent service and communication are considered very important to do. Both types of activities are central values that must be possessed when choosing a profession in the hospitality field. Program results show that attitudes gained from experience have a direct impact on workplace behavior and career development. In addition, such skills ultimately help increase productivity and efficiency in teams . In the future, problem-solving training is needed to improve participants' skills and abilities.